Voting Cohesion in the U.S. Civil War Congresses: The Role of Party and Regional Loyalty, 1861-1865 - Pollack, Daniel J. (My University, 2010)
To date, the history of the U.S. Civil War Congresses has been largely ignored. The legislative process has been overshadowed by a number of subjects, including biographies of important individuals, major battles, Emancipation, and the like. However, the project at hand provides focus to the Civil War Congresses and their legislative influences. Specifically, the House of Representatives abandon their pre-war regional loyalties in exchange for a system which emphasized strong partisan politics. The Senate, operating on different structural and procedural norms, was less reactive to the Civil War, but did experience a strengthened notion of partisan politics while maintaining some level of regional influence on specific types of legislation.
Keywords: United States. Congress--History--19th century; United States--Politics and government--1861-1865